2009
DOI: 10.1024/0300-9831.79.56.281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin C Supplementation on Oxidative Stress and Lipid Profiles in Hemodialysis Patients

Abstract: Every other day supplementation with 250 mg vitamin C for 12 weeks increases serum vitamin C, decreases MDA levels, and improves lipid profiles in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
3
32
0
1
Order By: Relevance
“…However, not all have been evaluated in clinical trials pertaining to alleviation of oxidative stress and endothelial dysfunction. To date, most clinical trials investigating the effects of supplementation on oxidative stress and endothelial dysfunction have focused on the traditional exogenous antioxidants vitamins C and E. As with aerobic exercise training, antioxidant therapies utilizing vitamins C and E have been shown in clinical trials to reduce systemic biomarkers of oxidative stress in both healthy adults (Mah et al, 2013) and patients with preexisting vascular diseases (Abdollahzad et al, 2009). In addition, administration of vitamins C and E has been shown in some (Skyrme-Jones, O'Brien, Berry, & Meredith, 2000) but not all studies (McKechnie, Rubenfire, & Mosca, 2002;Title, Cummings, Giddens, Genest, & Nassar, 2000) to acutely improve flowmediated dilation (FMD) in patients with preexisting endothelial dysfunction.…”
Section: Antioxidant Supplementationmentioning
confidence: 98%
“…However, not all have been evaluated in clinical trials pertaining to alleviation of oxidative stress and endothelial dysfunction. To date, most clinical trials investigating the effects of supplementation on oxidative stress and endothelial dysfunction have focused on the traditional exogenous antioxidants vitamins C and E. As with aerobic exercise training, antioxidant therapies utilizing vitamins C and E have been shown in clinical trials to reduce systemic biomarkers of oxidative stress in both healthy adults (Mah et al, 2013) and patients with preexisting vascular diseases (Abdollahzad et al, 2009). In addition, administration of vitamins C and E has been shown in some (Skyrme-Jones, O'Brien, Berry, & Meredith, 2000) but not all studies (McKechnie, Rubenfire, & Mosca, 2002;Title, Cummings, Giddens, Genest, & Nassar, 2000) to acutely improve flowmediated dilation (FMD) in patients with preexisting endothelial dysfunction.…”
Section: Antioxidant Supplementationmentioning
confidence: 98%
“…Ghiadoni et al, first reported that oral intake of a single high dose of vitamin C (2000 mg) significantly reduced OS biomarkers and subsequently increased antioxidant capacity of HD patients within 2 hours . Two randomized, placebo‐controlled trials reported that daily oral administration of 250 mg of vitamin C significantly reduced oxidative products in serum . Yang et al, showed that iv administration of 1000 mg of vitamin C before each HD session significantly decreased HD‐evoked OS in a group of 80 HD patients, while another study reported that both iv infusion of vitamin C and use of dialysate rich in vitamin C in chronic maintenance HD patients played a significant protective role against the HD‐mediated OS …”
Section: Therapeutic Interventions With Antioxidantsmentioning
confidence: 99%
“…This is mediated via their inhibition of cholesterol synthesis and LDL-cholesterol oxidation. [5860]…”
Section: Dietary Treatment Of Menopausementioning
confidence: 99%